Studi Komparatif Usahatani Cabe (Capsicum annum L) dengan dan Tanpa Menggunakan Pupuk Trichokompos di Kelurahan Guntung Manggis Kecamatan Landasan Ulin Kota Banjarbaru - Gusti Halimatus Sa'diah; Emy Rahmawati; Kamiliah Wilda (Universitas Lambung Mangkurat, 2013)
The study is aimed: (1) to distinguish the large chili cultivation between using and without using tricocompos; (2) to compare the cost, revenue and profit on both large chili cultivation; and (3) to identify the problems encountered by farmer at the study spot. Trichocompos is comprised of natural substance which can be used for fertilizer end pest controller, so it can reduce chemicals substance on the field. The tricocompos users generate profit as much as /DR 7. 42 million per farm, higher compared to non-user which only accounted IDR 5. 76 million per farm. The hindrances encountered on chili cultivation are the high vulnerability of chili from the exposure of pest, disease, and unpredictable extreme weather change. In addition, the tricocompos making is time consuming and require more labor.